Cysteine supplementation mitigates the toxicity associated with antitumor therapy of Ehrlich's ascites fluid adsorbed over protein a containing Staphylococcus aureus cowan I† - Ashish S Verma; Anchal Singh; Priyadarshini Mallick; Premendra D Dwivedi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Previously, we have reported the amelioration of ad-AF induced hepatotoxicity with the exogenous supplementation of glutathione (GSH) without compromising the anti-tumor effect of ad-AF in ascites tumor model of mice with transplantable Ehrlich's Ascites Tumor cells. Cellular uptake of glutathione (GSH) has its own limitations, therefore exogenous supplementation of L-cysteine (Cys) was tried to reduce the toxicity of ad-AF by providing -SH contents without compromising the anti-tumor property of adsorbed ascites fluid (ad-AF). Results: A significant increase in mean survival time (MST) of tumor bearing mice from 18.1 days to 32.9 days with exogenous supplementation of Cys was observed. Cys supplementation did not alter decline in body-weight gain, tumor cell counts as well as decrease in the viability of tumor cells in ascites tumor bearing animals. Similarly, Cys has been helpful to restore the hepatic -SH contents upto the levels of -SH content in tumor control group. The exogenous supplementation of Cys along with ad-AF has been helpful to restore the decline in the activities of phase-I and enhanced levels of glutathione-S-transferase (GST). The changes in the activities of different enzymes of phase-I and phase-II indicate the reduction in toxic insult induced by the therapeutic material (ad-AF). However, ad-AF treatment could not prevent tumor bearers from natural death due to tumor progression but significantly reduced the rate of tumor progression. Conclusions: Our study suggests that exogenous supplementation of Cys alongwith ad-AF could have a potential to be developed as a modality for the treatment of ascites tumor at least at experimental level.